JURIDICAL ANALYSIS OF THE MISUSE OF ELECTRONIC MEDICAL RECORDS IN THE PERSPECTIVE OF THE ELECTRONIC INFORMATION AND TRANSACTION LAW - Tryda Meutia Anwar; Jerry G. Tambun; Ahmad Jaeni (Law Faculty of Universitas Bandar Lampung, 2025)
The background of this research is regarding the potential for misuse of electronic medical records based on Electronic Information and Transactions (ITE) and patient data protection. Law Number 1 of 2024 concerning Information and Electronic Transactions which replaces Law Number 19 of 2016. And Law No. 27 of 2022 concerning Personal Data Protection. This research method uses qualitative and normative data analysis techniques. The results of this study show that Law Number 1 of 2024 concerning ITE is one of the important pillars that discusses the use of electronic information/documents as legal evidence at trial in the event of the dissemination of electronic medical records that can be used as illegal materials and to protect patients ' personal dataThere is Law No. 27 of 2022 concerning Personal Data Protection in Indonesia which has the main purpose of protecting individual personal data and regulating the collection, use, storage, security, and deletion of personal data by health services that manage patient data. By mandating strict data protection practices, the law upholds the ethical principle of patient confidentiality, which is essential for maintaining patient trust. Therefore, healthcare providers should invest in advanced cybersecurity measures.